Corporate entrepreneurial orientation and absorptive capacity as determinant of firm performance - Bernardus, Denny (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
This study examines the complicated relationship between company performance, absorptive ability, and corporate entrepreneurial orientation, taking institutional age into account. This research employs data analysis approaches utilizing variance-based structural equation modeling techniques (PLS-SEM). When absorptive capacity and corporate entrepreneurial orientation are high, firms under 10 years of age are anticipated to outperform older ones. Effective information absorption and entrepreneurial orientation help emerging institutions capitalize on external knowledge and sustain their entrepreneurial spirit. This study underlines the need for empirical research to support theoretical ideas by addressing industry dynamics, organizational culture, and leadership styles. Such a study would inform strategic decision making and organizational practices, helping institutions operate better in dynamic commercial situations.